The Effectiveness of E-Learning Interventions in Enhancing Parental Knowledge and Attitudes Toward Exclusive Breastfeeding: A Narrative Review for Implementation in the Indonesian Context - Elvaro Islami Muryadi Muryadi; Radhakrishnan Muthukumar; Isaraporn Thepwongsa; Pattapong Kessomboon (Public Health of Indonesia, 2026)
Background: Exclusive breastfeeding provides substantial health benefits for infants and mothers; however, adherence rates remain suboptimal worldwide. Barriers such as limited access to healthcare services, inadequate prenatal education, and insufficient involvement of fathers continue to undermine breastfeeding practices. Objectives: This narrative review aims to critically synthesize global evidence on e-learning interventions for exclusive breastfeeding education and explore their effectiveness, contextual determinants, and implementation challenges relevant to Indonesia. Methods: A narrative review was conducted using PubMed, Scopus, ScienceDirect, and Google Scholar (2015–2024). Of 187 identified articles, 29 met the inclusion criteria and were thematically analyzed to evaluate e-learning interventions and barriers to exclusive breastfeeding education. Results: The findings demonstrate that e-learning interventions can improve parental knowledge and breastfeeding self-efficacy; however, their impact on sustained exclusive breastfeeding behavior remains variable. Interventions incorporating multimedia content, interactive engagement, and personalized digital support tend to yield stronger outcomes than passive formats. Father-inclusive approaches are consistently associated with improved parental alignment and breastfeeding continuation. Nevertheless, effectiveness is moderated by technological access, digital literacy, healthcare system integration, and sociocultural factors, particularly in low-resource and rural settings. Conclusion: E-learning interventions offer a potentially scalable approach to promoting exclusive breastfeeding; however, their effectiveness is highly context-dependent. In settings such as Indonesia, digital strategies must be culturally adapted, family-inclusive, and integrated within existing healthcare and community support systems to achieve meaningful and equitable impact. Rather than functioning as standalone solutions, e-learning frameworks should complement structural and relational determinants of breastfeeding behavior. Future initiatives should prioritize contextual adaptation, technological equity, and rigorous evaluation to inform sustainable program development and policy decisions.